ضوابط البناء في الفقه الإسلامي - Saleh, S.F.; Alwi, A.A.Z.A. (Universiti Sains Islam Malaysia, 2024)
Islamic law has urged for the reconstruction of earth for the purpose of worshiping Allah and the continuity of life. One task through which this purpose can be achieved is the construction of buildings. Islamic law has shown that the construction of buildings is one of the goals of this law that helps to cover the loins and protect from the coldness of winter and the hotness of summer. However, there are some Islamic constraints on the construction of buildings that have to be taken in consideration. The current study addresses the Islamic constraints on the construction of buildings from different perspectives. First, the study provides a definition of the construction of buildings, its importance, and its rules. Second, the study provides a discussion of the Islamic constraints on the construction of buildings.